Teacher Mentoring in Developing Outcome-Based Education Teaching Modules Integrated with Local Wisdom in the Implementation of the Merdeka Curriculum at SMP Negeri 12 Mataram - Lukman Lukman; Junaidin Junaidin; Furkan Furkan; Sopian Aulia; Dea Ananta M; Dian Lindri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This community service activity aims to improve teachers' ability in developing teaching modules based on Outcome-Based Education (OBE) integrated with local wisdom as an implementation of the Merdeka Curriculum. The approach used was direct mentoring through workshops and technical guidance involving 20 teachers at SMP Negeri 12 Mataram, West Nusa Tenggara. The implementation method included socialization of OBE and Merdeka Curriculum concepts, training in module development, and mentoring in local wisdom integration. Data were collected through pretest and posttest to measure improvements in teacher competency. The results showed a significant increase from an average pretest score of 70.15 to 85.05 in the posttest, with an average improvement of 14.90 points. These findings indicate that the mentoring program was effective in enhancing teachers' capacity to develop relevant, contextual, and culturally enriched teaching modules in the spirit of the Merdeka Curriculum.